2015
DOI: 10.1177/0264550515619572
|View full text |Cite
|
Sign up to set email alerts
|

Young people, peer-to-peer grooming and sexual offending

Abstract: There is ample evidence that young people are using social media in grooming and bullying to abuse and exploit others sexually with enough frequency to make those behaviours important concerns for both society and care providers. This article provides a critical overview of the conceptual and theoretical foundations for 'grooming' among peers and use of social media within harmful sexual behaviour. It introduces a model for intervention based on the literature on memory, bundles, thinking and problem solving a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…of JSO who sexually harassed victims exclusively verbally and/or via the Internet. Although adolescent online sexual offending has gained in significance and the number of corresponding offenses has increased over the last decade (Ashurst & McAlinden, 2015;Boonmann et al, 2014;Mohler-Kuo et al, 2014), no study to date has deduced the existence of a specific JSO verbal/online-offender subtype based on empirical data. Furthermore, our results indicate that JSO subgroups differ in their rates of criminal reoffending (including sexual re-offending).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…of JSO who sexually harassed victims exclusively verbally and/or via the Internet. Although adolescent online sexual offending has gained in significance and the number of corresponding offenses has increased over the last decade (Ashurst & McAlinden, 2015;Boonmann et al, 2014;Mohler-Kuo et al, 2014), no study to date has deduced the existence of a specific JSO verbal/online-offender subtype based on empirical data. Furthermore, our results indicate that JSO subgroups differ in their rates of criminal reoffending (including sexual re-offending).…”
Section: Discussionmentioning
confidence: 99%
“…Even though recent research highlights the frequency and significance of Internet-based forms of sexual coercion among today's adolescents (e.g. sexual harassment via cell phone; Ashurst & McAlinden, 2015;Mohler-Kuo et al, 2014), we are not aware of any comprehensive JSO study revealing an empirically derived subtype of juveniles who have exclusively committed online sex offenses.…”
Section: Empirical Subtyping Approachesmentioning
confidence: 97%
See 1 more Smart Citation
“…Body-shaming and slutshaming are considered the most common sub-forms of appearance-shaming (Mayer & Vanderheiden, 2021). Publicly shaming one's appearance is common among adolescents and happens both offline at school (Ashurst & McAlinden, 2015;Gam et al, 2020;Lestari, 2019;Lickteig, 2021) and on social media (Lestari, 2019). This practice has been associated with serious consequences for a victim's self-esteem, body surveillance, and selfobjectification (Gam et al, 2020;McMahon et al, 2022).…”
Section: Celebrity Bashing and Body-shamingmentioning
confidence: 99%
“…Although literature in this area is growing, there are inconsistencies in what motivates young people to participate in sexting. Studies have revealed a diverse range of motivations including for pleasure, to flirt, to express sexual desire (Phippen, 2012;Lippman and Campbell, 2014;Lee and Crofts, 2015;Van Ouytsel et al, 2017); peer pressure, for revenge or blackmail (Ringrose et al, 2013;Ashurst and McAlinden, 2015;Englander, 2015); for attention, "fun" or "as a joke" (Mitchell et al, 2012: 17) and, as a symbol of trust within a relationship or to make their partner happy (Albury and Crawford, 2012). The wide range of motivations reinforces the complexity of the sexual behaviour and the variety of pressures young people are exposed to.…”
Section: Introductionmentioning
confidence: 99%